2021
DOI: 10.1016/j.isci.2021.103350
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA CDK6-AS1 overexpression impacts on acute myeloid leukemia differentiation and mitochondrial dynamics

Abstract: Summary Patients with acute myeloid leukemia (AML) carrying high-risk genetic lesions or high residual disease levels after therapy are particularly exposed to the risk of relapse. Here, we identified the long non-coding RNA CDK6-AS1 able to cluster an AML subgroup with peculiar gene signatures linked to hematopoietic cell differentiation and mitochondrial dynamics. CDK6-AS1 silencing triggered hematopoietic commitment in healthy CD34+ cells, whereas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The first contained a total of 140 adult AML patients, 7 of which harbored the RUNX1/RUNX1T1 fusion (GEO accession, GSE37642; Platform, GPL570) [ 23 , 24 , 25 , 26 ]. The second contained 16 pediatric AML patients harboring the RUNX1/RUNX1T1 fusion out of a total of 48 AML patients (GSE75461; Platform, GPL17586) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first contained a total of 140 adult AML patients, 7 of which harbored the RUNX1/RUNX1T1 fusion (GEO accession, GSE37642; Platform, GPL570) [ 23 , 24 , 25 , 26 ]. The second contained 16 pediatric AML patients harboring the RUNX1/RUNX1T1 fusion out of a total of 48 AML patients (GSE75461; Platform, GPL17586) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, AML patients with the highest CDK6-AS1 levels were at high risk of not achieving complete remission, and also had elevated expression of mitochondrial translation-related genes, while being negatively enriched in genes regulated by RUNX1, an essential factor for the early hematopoietic differentiation process. Functionally, it was proven that CDK6-AS1 depletion promoted the differentiation of CD34 + cells, demonstrating no effect on cell viability, but inducing a reduction in the colony-forming capacity of AML cells [ 78 ].…”
Section: Non-coding Rna-regulation Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…Overall, these findings suggest that aberrant expression of CDK6-AS1 maintains more immature leukemic stem cell subsets with elevated mitochondrial activities to address high energy demand, inducing drug resistance and apoptosis escape. CDK6-AS1 expression, correlating with mitochondrial status, could thus allow to discriminate AML patients benefitting from the combination of chemotherapy with mitochondria-targeting agents [ 78 ].…”
Section: Non-coding Rna-regulation Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…A recent elaborate study has identified lncRNA CDK6-AS1 as a novel regulator in pediatric AML [ 60 ]. In a pediatric patient cohort, CDK6-AS1 was significantly overexpressed and associated with higher minimal residual disease after induction therapy.…”
Section: Lncrnas In Pediatric Amlmentioning
confidence: 99%
“…Interestingly, mitochondrial targeting, using Tigecycline, sensitizes AML blasts with high CDK6-AS1 expression to chemotherapy, supporting the concept of a mitochondrial vulnerability in these blasts. Overall, these findings identified CDK6-AS1 as an important regulator of early hematopoietic differentiation and leukemogenesis of pediatric AML and uncovered therapeutics targeting mitochondrial biogenesis as a novel treatment strategy in pediatric AML [ 60 ].…”
Section: Lncrnas In Pediatric Amlmentioning
confidence: 99%